Glyphosate Mimics 17β-Estradiol Effects Promoting Estrogen Receptor Alpha Activity in Breast Cancer Cells - Mera-Adasme, R (Elsevier Ltd, 2023)
Glyphosate, the active ingredient in several broad-spectrum herbicide formulations, has been validated and widely used throughout the world. Recent reports have questioned its safety, showing that glyphosate may act as an endocrine disruptor by promoting estrogenic activity. However, the molecular mechanism involved in this phenomenon remains unclear. Therefore, here we aimed to elucidate the mechanism by which glyphosate induces estrogenic activity using estrogen-sensitive breast cancer cell line models. Our results show that glyphosate mimics the cell effects of 17β-estradiol (E2), promoting estrogen receptor α (ERα) phosphorylation, its degradation, and transcriptional activity at high concentrations. The molecular mechanism seems involved in the ERα ligand-binding domain (LBD). Molecular simulations suggest a plausible interaction between glyphosate and the LBD through a coordinated complex involving divalent cations such as Zn (II). In addition, glyphosate exposure alters the level of Cyclin-dependent kinase 7 that contribute to ERα phosphorylation. Finally, glyphosate increases cell proliferation rate and levels of cell cycle regulators, accompanied by an increase in anchorage-independent growth capacity. These findings suggest that glyphosate at high concentrations, induces estrogen-like effects through an ERα ligand binding site-dependent mechanism, leading to cellular responses resulting from a complex interplay of genomic and non-genomic events. © 2022 Elsevier Ltd